Experimental and Kinetic Modeling Study of Cyclohexane and Its Mono-alkylated Derivatives Combustion - Wang, Zhandong; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2018)
This thesis investigates the combustion chemistry of cyclohexane, methylcyclohexane, and ethylcyclohexane on the basis of state-of-the-art synchrotron radiation photoionization mass spectrometry experiments, quantum chemistry calculations, and extensive kinetic modeling. It explores the initial decomposition mechanism and distribution of the intermediates, proposes a novel formation mechanism of aromatics, and develops a detailed kinetic model to predict the three cycloalkanes$1 (Bcombustion properties under a wide range of conditions. Accordingly, the thesis provides an essential basis for studying much more complex cycloalkanes in transport fuels and has applications in engine and fuel design, as well as emission control.s
Keywords: Mechanical Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Atmospheric Protection/Air Quality Control/Air Pollution; Physical Chemistry